ANTIBACTERIAL EFFECTIVENESS OF LIME PEEL (Citrus hystrix) EXTRACT GEL ON Porphyromonas gingivalis BACTERIES - M. Rizky Nuari Asmik Ara; Beta Widya Oktiani; Ika Kusuma Wardani; Renie Kumala Dewi; Fransiska Uli Arta Panjaitan (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Periodontitis is an inflammation of the tooth-supporting tissues caused by microorganisms, especially Porphyromonas gingivalis. Porphyromonas gingivalis has resistance to many antibiotics. Kuit lime peel has potential as an antibacterial with the most compound content is triterpenoid. Objective: To measure and analyze the effectiveness of antibacterial gel of kuit lime peel extract (Citrus hystrix) on the growth of Porphyromonas gingivalis bacteria. Methods: This study is a laboratory experimental study with post test with control group design, using seven treatment groups, namely 5%, 10%, 20% kecapi leaf extract, and metronidazole positive control with 7 repetitions of each treatment. Antibacterial effectiveness uses the disc diffusion method which is seen from the diameter of the inhibition zone formed on Mueller Hinton Agar media. Results: Based on the results of Kruskal-Wallis and Post hoc Mann Whitney tests, there were significant differences between concentration groups of 5%, 10%, 20%, and metronidazole. Conclusion: Lime peel extract gel (Citrus Hystrix) concentrations of 5%, 10%, and 20% have antibacterial potential against Porphyromonas gingivalis bacteria. Keywords: kuit lime peel extract, antibactery, porphyromonas gingivalis